FORMATION OF COMMUNICATIVE COMPETENCIES OF PRIMARY CLASS STUDENTS ON THE BASIS OF THE PIRLS INTERNATIONAL ASSESSMENT PROGRAM - Ne’matova Flora Baxtiyor Qizi (Journals Park Publishing, 2024)
In the era of rapid globalization, educational systems worldwide are adapting to meet the evolving demands of modern society. This article explores the formation of communicative competencies among primary class students, emphasizing the role of the Progress in International Reading Literacy Study (PIRLS) assessment program. It examines the educational reforms in Uzbekistan, driven by strategic goals to enhance reading literacy and overall communicative skills in alignment with international standards. The integration of technology in education is highlighted as a key factor in developing these competencies. The article underscores the significance of targeted interventions, innovative teaching strategies, and policy reforms in preparing students to succeed in an increasingly interconnected world.
Keywords: Communicative competencies, primary education, PIRLS, reading literacy, educational reforms, Uzbekistan, globalization, technology integration.